Polycyclic aromatic hydrocarbons and trace elements bounded to airborne PM10 in the harbor of Volos, Greece: Implications for the impact of harbor activities. (October 2017) - Manoli, E.; Chelioti-Chatzidimitriou, A.; Karageorgou, K.; Kouras, A.; Voutsa, D.; Samara, C.; Kampanos, I.
Abstract: Harbors are often characterized by high levels of air pollutants that are emitted from ship traffic and other harbor activities. In the present study, the concentrations of Polycyclic Aromatic Hydrocarbons (PAHs) and trace elements (As, Cd, Ni, Pb, Cr, Mn, Zn, and Fe) bounded to the inhalable particulate matter PM10 were studied in the harbor of Volos, central Greece, during a 2-year period (2014–2015). Seasonal and daily variations were investigated. Moreover, total carcinogenic and mutagenic activities of PAHs were calculated. The effect of major wind sectors (sea, city, industrial, harbor) was estimated to assess the potential contribution of ship traffic and harbor activities, such as scrap metal handling operations. Results showed that the harbor sector (calm winds ≤ 0.5 m s −1 ) was associated with the highest concentrations of PM10 . The harbor sector was also associated with relatively increased levels of trace elements (As, Fe, Cr, Mn, Ni), however the effect of this sector was lower than the corresponding effect of the industrial wind sector. The sea sector showed only a slight increase in B[ a ]Py and Σ12 PAHs, whereas the highest increasing effect for PAHs and traffic-related elements, such as Pb and Zn, was evidenced for the city sector. Graphical abstract: Highlights: PM10 and bounded PAHs and trace elements were investigated in Volos harbor, Greece. The effect of major wind sectors (city, sea, industrial, harbor) was estimated. PAHs, Pb, Zn and Cd were strongly affected by the city sector. The sea sector showed a slight increase in B[ a ]Py and total PAHs. As, Fe, Cr, Mn, Ni were affected by the industrial sector and scrap metal handling.